Anti-Oxidant Multi-Functionalized Materials: Strontium-Substituted Monetite and Brushite as Delivery Systems for Curcumin - Francesca Silingardi; Stefania Pagani; Alessandro Gambardella; Gianluca Giavaresi; Adriana Bigi; Elisa Boanini (MDPI AG, 2023)
Curcumin has numerous biological activities and pharmaceutical applications related to its ability to inhibit reactive oxygen species. Herein, strontium-substituted monetite (SrDCPA) and strontium-substituted brushite (SrDCPD) were synthesized and further functionalized with curcumin with the aim to develop materials that combine the anti-oxidant properties of the polyphenol, the beneficial role of strontium toward bone tissue, and the bioactivity of calcium phosphates. Adsorption from hydroalcoholic solution increases with time and curcumin concentration, up to about 5-6 wt%, without affecting the crystal structure, morphology, and mechanical response of the substrates. The multi-functionalized substrates exhibit a relevant radical scavenging activity and a sustained release in phosphate buffer. Cell viability, morphology, and expression of the most representative genes were tested for osteoclast seeded in direct contact with the materials and for osteoblast/osteoclast co-cultures. The materials at relatively low curcumin content (2-3 wt%) maintain inhibitory effects on osteoclasts and support the colonization and viability of osteoblasts. The expressions of Alkaline Phosphatase (ALPL), collagen type I alpha 1 chain (COL1A1), and osteocalcin (BGLAP) suggest that curcumin reduces the osteoblast differentiation state but yields encouraging osteoprotegerin/receptor activator for the NFkB factor ligand (OPG/RANKL) ratio.